2015
DOI: 10.1007/s10895-015-1664-4
|View full text |Cite
|
Sign up to set email alerts
|

A New Isoindoline Based Schiff Base Derivative as Cu(II) Chemosensor: Synthesis, Photophysical, DNA Binding and Molecular Docking Studies

Abstract: A new chemo sensor 2-(4-methylbenzylideneamino)-isoindoline-1,3-dione (PDB) was synthesized and characterized by UV-Vis., IR, (1)H NMR, (13)C NMR spectral and elemental analysis. Its photophysical properties in organic solvents with different polarity were studied. The sensitivity of the PDB in different pH solutions was investigated and the results indicated that PDB would be able to act as an efficient "off-on-off" switch for pH. This chemosensor displayed high selectivity towards Cu(2+) in the presence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 42 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…The CD spectrum of ct‐DNA exhibits a positive band at ∼275 nm due to base stacking and a negative band at ∼245 nm due to the right‐handed helicity of B‐DNA form which are sensitive to interactions with small molecules. It has been well documented that groove binding and electrostatic interaction of small molecules show less or no perturbation on the base stacking and helicity bands, whereas intercalation alters the intensities of both the bands significantly, thus stabilizing the right‐handed B conformation of DNA . The CD spectra of ct‐DNA with the increasing concentrations of 8 k are shown in Figure (f) .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The CD spectrum of ct‐DNA exhibits a positive band at ∼275 nm due to base stacking and a negative band at ∼245 nm due to the right‐handed helicity of B‐DNA form which are sensitive to interactions with small molecules. It has been well documented that groove binding and electrostatic interaction of small molecules show less or no perturbation on the base stacking and helicity bands, whereas intercalation alters the intensities of both the bands significantly, thus stabilizing the right‐handed B conformation of DNA . The CD spectra of ct‐DNA with the increasing concentrations of 8 k are shown in Figure (f) .…”
Section: Resultsmentioning
confidence: 90%
“…It has been well documented that groove binding and electrostatic interaction of small molecules show less or no perturbation on the base stacking and helicity bands, whereas intercalation alters the intensities of both the bands significantly, thus stabilizing the righthanded B conformation of DNA. [26] The CD spectra of ct-DNA with the increasing concentrations of 8 k are shown in Figure 3(f). As it can be observed that upon addition of compound 8 k, CD spectra is not significantly perturbed indicating groove binding between ct-DNA and 8 k. The little change in the intensity of the graph might be due to certain conformational changes such as the conversion of DNA from a more B-like to a more A-like structure.…”
Section: Fluorimetric Studiesmentioning
confidence: 99%
“…The ionochromic behavior of Schiff bases and the interaction with a wide range of metal ions have been well documented [44]. Schiff bases containing salicyaldimine based ligands can be used in the development of cost-effective chemosensors because they show significant color changes of the solution and maxima of the absorption bond when they interact with anions and cations [45][46]. Recently, we reported aneasy and applicable method for the preparation [47] and use of low cost chemosensors based on Schiff bases for the selective detection of some toxic metal ions and anions [48,49].…”
mentioning
confidence: 99%
“…As part of our research work, aimed at designing and developing biologically active cyclic imides, herein we describe the antibacterial and DNA‐binding studies of some novel N ‐substituted phthalimide derivatives. These newly synthesized compounds have been screened for their scavenging capacity against DPPH and hydrogen peroxide free radicals and the results were compared with ascorbic acid as a synthetic antioxidant.…”
mentioning
confidence: 99%